2000
DOI: 10.1017/s1355838200991994
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of TAP interacts with the nuclear pore complex and promotes export of specific CTE-bearing RNA substrates

Abstract: Messenger RNAs are exported from the nucleus as large ribonucleoprotein complexes (mRNPs). To date, proteins implicated in this process

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
387
4
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(412 citation statements)
references
References 65 publications
20
387
4
1
Order By: Relevance
“…Tap can bind a number of nucleoporins in vitro including p62, Can/ Nup214, Nup98, RanBP2, and CG1 (Katahira et al, 1999;Bachi et al, 2000;Lévesque et al, 2001;Katahira et al, 2002;Grant et al, 2003;Forler et al, 2004). Using a solid-phase binding assay, we have observed that Nxt1 could stimulate binding of both cargo-free Tap and the Tap/CTE RNA complex to p62 .…”
Section: Formation Of Tap/cte Rna Complexes On Nucleoporinsmentioning
confidence: 94%
See 1 more Smart Citation
“…Tap can bind a number of nucleoporins in vitro including p62, Can/ Nup214, Nup98, RanBP2, and CG1 (Katahira et al, 1999;Bachi et al, 2000;Lévesque et al, 2001;Katahira et al, 2002;Grant et al, 2003;Forler et al, 2004). Using a solid-phase binding assay, we have observed that Nxt1 could stimulate binding of both cargo-free Tap and the Tap/CTE RNA complex to p62 .…”
Section: Formation Of Tap/cte Rna Complexes On Nucleoporinsmentioning
confidence: 94%
“…Tap also mediates nuclear export of certain retroviral mRNAs, such as the Mason-Pfizer monkey virus (MPMV; Grü ter et al, 1998). A cis-acting element in the noncoding 3Ј region of these viral transcripts, known as the constitutive transport element (CTE), forms a stem-loop structure recognized by Tap (Bray et al, 1994;Ernst et al, 1997aErnst et al, , 1997bGrü ter et al, 1998;Braun et al, 1999;Bachi et al, 2000;Liker et al, 2000). In contrast, the interaction between Tap and eukaryotic mRNAs appear to require a number of adaptor proteins that are recruited to messenger ribonucleoprotein (mRNP) complexes during transcription and processing (Izaurralde, 2002;Cullen, 2003;Stutz and Izaurralde, 2003;Vinciguerra and Stutz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While one cannot actually prove selection from a retrospective analysis of a single region, several features of the data are suggestive. S48 sits in a poorly conserved region of Nxf1 that is not essential to Nxf1 biochemical function 23 . In contrast, E610 is highly conserved among vertebrates and sits in a UBA domain thought to mediate nuclear export through physical interaction with the nuclear pore and exhibits a significant chemical shift upon binding FG peptide 24,25 (Figure 5b-d).…”
Section: Nxf1 Cast Is a Natural Allele And Polymorphic In Wild Populamentioning
confidence: 99%
“…Prior to their export into the cytoplasm, the primary transcripts of protein-encoding eukaryotic genes (premRNAs) require extensive processing into mRNAs, including the removal of intronic sequences and the addition of a cap structure to the 59 end and a poly(A) tail to the 39 of the transcript+ Presumably, cells have evolved mechanisms to coordinate these processing events to improve the efficiency of each step and to ensure that only fully and correctly processed transcripts are translated into protein+ Early evidence for a coupling between splicing and downstream events came from the observation that the presence of an intron promotes expression of trans-genes in metazoan cells (Matsumoto et al+, 1998)+ More recently, this effect has been attributed to an enhancement in the rate of export of mRNAs that have undergone splicing, relative to mRNAs derived from non-intron-containing genes (Luo & Reed, 1999)+ In the same study, it was proposed that the increased export efficiency was due to assembly of the mRNA with specific RNA-binding proteins as a result of splicing+ Shortly thereafter, the identification of a multiprotein complex, referred to as the exon-junction complex (EJC) was reported+ This complex is deposited in a sequence-independent, but position-specific manner ;20 nt upstream of exon-exon junctions concomitant with, or immediately following, in vitro splicing (Le Hir et al+, 2000)+ The EJC was suggested to serve as a marker for properly spliced and thus export-competent mRNAs+ Consistent with this notion, one of the components was identified as Aly (also known as REF), a small RNAbinding protein implicated in mRNA export in metazoans (Le Hir et al+, 2000;Stutz et al+, 2000;Zhou et al+, 2000)+ Aly/REF directly interacts with the conserved mRNA export factor TAP (Stutz et al+, 2000)+ TAP in turn interacts with components of the nuclear pore complex, the site of transport of macromolecules between the nucleus and the cytoplasm (Kang & Cullen, 1999;Bachi et al+, 2000)+ As expected for a bona fide mRNA export carrier, TAP continuously shuttles between these two compartments (Bear et al+, 1999)+ Another link between pre-mRNA splicing and export was uncovered when UAP56, a factor originally implicated in spliceosome assembly, was subsequently shown to be also required for efficient mRNA export (Gatfield et al+, 2001;Luo et al+, 2001)+ UAP56 is a member of the DEAD-box family of ATPases+ These enzymes have been demonstrated to promote changes in RNA-RNA and, more recently, RNA-protein interactions that drive multistep reactions such as translation, pre-mRNA splicing, and ribosomal RNA processing (for review, see Staley & Guthrie, 1998;Linder et al+, 2001)+ Strikingly, in vitro experiments demonstrated that UAP56 can interact directly with Aly, and that association of UAP56 with newly spliced mRNA can be detected prior to Aly in time-course experiments (Luo et al+, 2001)+ In addition, mutant forms of Aly that are unable to...…”
Section: Introductionmentioning
confidence: 99%